Photo-spin-voltaic effect in PtMn/Y3Fe5O12 thin films. (9th December 2020) - Yadav, Roshni; Shepit, Michael; Li, Xu; Lin, Ko-Wei; van Lierop, Johan; Ruotolo, Antonio
Abstract: The photo-spin-voltaic effect is revealed by the presence of a spin voltage generated by photons when a non-magnetic metal (e.g., Pt) is in close proximity to a ferrimagnetic insulator (e.g., Y3 Fe5 O12 (YIG)). This is attributed to the excited electrons and holes diffusing from the proximized layer near the interface to the metallic surface. By using a dual-ion-beam sputtering deposition technique, a metallic PtMn layer was deposited on YIG /Gd3 Ga5 O12 (GGG) (111) substrates. We report on the photo-induced-spin voltaic effect in a PtMn/YIG/GGG heterostructure. The sign of the photo-generated voltage was found to switch with magnetic field polarity and its intensity to decrease with increasing PtMn thickness. This indicates that spin-polarized electrons are confined near the interface in the metal. Photo-excitation of these carriers, together with spin–orbit coupling with Pt atoms, is at the origin of the measured transverse voltage. The design may find applications in antiferromagnetic spintronics.